Breaking the sound barrier - Ang, Hui Xuan (2017)
This paper presents Breaking The Sound Barrier (BTSB), a campaign to encourage more employers to hire the deaf, initiated by four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. It aimed to create positive attitudes towards hiring the deaf by highlighting that the deaf are as capable as the hearing. The campaign targeted people involved in the hiring process, such as managers and Human Resource (HR) personnel, who had no intentions to hire the deaf and were not doing so.